Excellent Service: Studi Implementasi pada Koperasi Syariah - Mahendra Dwi Laksono; Sri Mulyani (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
Excellent Service is an effort to keep customers always using the services of BMT Al-Hijrah KAN Jabung Syariah Wates Branch Office, Exellent Service BMT Al-Hijrah KAN Jabung Syariah Wates Branch Office is expected to be able to dominate market share in order to attract new customers to increase and maintain customers who have long used the services of BMT Al-Hijrah KAN Jabung Syariah Wates Branch Office in the world of conventional financial institution market competition. Researchers use a qualitative methodology with a case study approach, using dissected information not in a numerical framework. Data collection techniques are carried out by collecting data, data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of excellent service at BMT Al-Hijrah KAN Jabung Wates Branch in the Security, Customer Service, Teller and AO sections is in accordance with the concept of excellent service in financial institutions in general.